2010
DOI: 10.1097/psy.0b013e3181d2f0dd
|View full text |Cite
|
Sign up to set email alerts
|

Partner Violence and Psychological Well-Being: Buffer or Indirect Effect of Social Support

Abstract: Psychological well-being was independently affected by IPV (types and duration) and social support (friends network size, tangible support). Only family network size mitigates the negative consequences of IPV on self-perceived health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 30 publications
7
38
1
4
Order By: Relevance
“…This finding is in agreement with those in the literature showing that social support protects against the deleterious effects of IPV on women's health, increases the likelihood that women will take actions to eliminate IPV (Campbell et al, 1995;Chang et al, 2010;Coker et al, 2002;Escrib a-Ag€ uir et al, 2010;Mburia-Mwalili, ClementsNolle, Lee, Shadley, & Wei, 2010), and decreases the risk of partner revictimization (Bybee & Sullivan 2002;2005). Thus, these studies highlight the buffering effects that social support has on the impact of IPV on women's health and its beneficial effects regarding recovery from IPV over time.…”
Section: Factors That Improve Physical Healthsupporting
confidence: 93%
“…This finding is in agreement with those in the literature showing that social support protects against the deleterious effects of IPV on women's health, increases the likelihood that women will take actions to eliminate IPV (Campbell et al, 1995;Chang et al, 2010;Coker et al, 2002;Escrib a-Ag€ uir et al, 2010;Mburia-Mwalili, ClementsNolle, Lee, Shadley, & Wei, 2010), and decreases the risk of partner revictimization (Bybee & Sullivan 2002;2005). Thus, these studies highlight the buffering effects that social support has on the impact of IPV on women's health and its beneficial effects regarding recovery from IPV over time.…”
Section: Factors That Improve Physical Healthsupporting
confidence: 93%
“…Psychological violence can also result in individuals being restricted from social support, which further diminishes identity and control (Escriba-Aguir et al, 2010). Again, this is pertinent in the link between psychological IPV and subsequent PTSD given that social support in the aftermath of traumatic experience is a known protective factor in the development of PTSD symptoms (Karstoft, Armour, Elklit, & Solomon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that actual and perceived social support can act as a buffer against the harmful effects of traumatic experiences (Escribá-Agüir et al, 2010; Ozer et al, 2003). Thus, increasing social support may be an important therapeutic target.…”
Section: Discussionmentioning
confidence: 99%